2011
DOI: 10.1007/s10495-011-0660-7
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of checkpoint kinase 1 abrogates G2/M checkpoint activation and promotes apoptosis under heat stress

Abstract: Hyperthermia induced by heat stress (HS) inhibits the proliferation of cancer cells and induces their apoptosis. However, the mechanism underlying HS-induced apoptosis remains elusive. Here, we demonstrated a novel evidence that checkpoint kinase 1 (Chk1) plays crucial roles in the apoptosis and regulation of cell cycle progression in cells under HS. In human leukemia Jurkat cells, interestingly, the ataxia telangiectasia and Rad-3 related (ATR)-Chk1 pathway was preferentially activated rather than the ataxia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 37 publications
(52 reference statements)
7
43
0
Order By: Relevance
“…Activation of Rad3 ensures that Chk1 kinase remains in a hypo-phosphorylated state thereby preventing premature mitosis under heat stress conditions. These findings are consistent with a recent report showing that ATR Rad3 -to-Chk1 signalling is activated when human cells are exposed to elevated temperatures (Furusawa et al, 2011). Which heat alterations stimulate ATR is unknown and its signalling output is the phosphorylation of Chk1 at S345 and not its dephosphorylation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Activation of Rad3 ensures that Chk1 kinase remains in a hypo-phosphorylated state thereby preventing premature mitosis under heat stress conditions. These findings are consistent with a recent report showing that ATR Rad3 -to-Chk1 signalling is activated when human cells are exposed to elevated temperatures (Furusawa et al, 2011). Which heat alterations stimulate ATR is unknown and its signalling output is the phosphorylation of Chk1 at S345 and not its dephosphorylation.…”
Section: Discussionsupporting
confidence: 92%
“…An increase in reactive oxygen activates ATM directly in the absence of the MRN complex by inducing the formation of a disulfide-crosslinked dimer (Guo et al, 2010). The cellular targets of ATM at high temperatures remain to be identified, but they may be linked with apoptosis (Furusawa et al, 2011) or a prolonged G2-M arrest (Zölzer and Streffer, 2001). …”
Section: Introductionmentioning
confidence: 99%
“…6A). ATR-Chk1 pathway is a critical regulator of the cellular response to DNA damage and replication stress, and interruption of this signaling may result in the impairment of the S-phase checkpoint function and also abrogate G 2 -M checkpoint activation (26). Thus, we wondered whether Pol k could impact S or G 2 checkpoint responses to temozolomideinduced DNA damage.…”
Section: Pol K Depletion Induces a Delay In Hr-mediated Dna Repairmentioning
confidence: 99%
“…Alternatively, hyperthermia can create chromosomal lesions which if not removed during mitosis can result in triggering cell death pathways [38].…”
Section: Indirect Effectsmentioning
confidence: 99%
“…Following ATM activation, 53BP1 interacts with its effector molecule, RIF1, which is recruited at the sites of DSBs and is also antagonized by BRCA1 and CtIP leading to the induction of the appropriate DNA repair pathway(s) [47]. Moreover, hyperthermia has been shown to delay the employment of 53BP1 in MRN complex formation [23] whereas activation of ATM is decelerated after heat exposure [38]. Furthermore, data from other reports have associated the activation of ATM with generation of oxidative stress as it was shown that ROS can oxidize the disulfide bond between the monomers of the ATM dimer without the presence of MRN and thus causing directly its activation [48].…”
Section: Indirect Effectsmentioning
confidence: 99%